Urethral Steinstrasse following Laser Lithotripsy of Prostatic Urethral Calculi - Jennifer Den; Preston S. Kerr; Tamer J. Dafashy; Christopher D. Kosarek; Robyn L. Roberts; J. Nicholas Sreshta (Case Reports in Urology)
Symptomatic prostatic calculi are rare occurrences with several management options, the most popular of which is currently transurethral laser lithotripsy. This is a generally well-tolerated procedure with minimal complications. To date, no reported episodes of steinstrasse at the urethral level following prostatic calculi lithotripsy have been documented to our knowledge. We report a unique case of acute urinary retention secondary to obstructive calculi fragments following a transurethral laser lithotripsy of large prostatic calculi, further complicated by stricture at the fossa navicularis.